Theoretical Semi-Empirical Studies of Electronic Structures of Schiff Bases of Cyanoethylatedbenzaldehyde - ARORA, KISHOR; SHARMA, K.P.; SHARMA, MUKESH (Asian Journal of Chemistry, 2010)
Present communication reports theoretical semi-empirical AM1 studies of some Schiff bases of 2-methyl-4-NN-bis-2'- cyano ethylaminobenzaldehyde along with their comparison with their parent compounds. Theoretical studies reveal that it is azomethine group in the Schiff bases under study, that acts as site for coordination to metals as reported by many coordination and bioinorganic chemists.